ANALISIS MODEL BANGKITAN DAN TARIKAN PERGERAKAN KABUPATEN ROKAN HULU - Ramdhani, Fitra; Tisnawan, Rahmat (Universitas Abdurrab, 2018)
ABSTRACT Rokan Hulu regency is a regency from region expansion of Kampar regency with Pasir Pangaraian as a capital of regency, Riau Province. Development of transportation in this area should be able to support the efforts of equity and the spread of regional development. This is because the fulfillment of the available needs are located elsewhere so as to affect the magnitude of trip generation and trip attraction. The analysis of the model of trip generation and trip attraction by using a model of zone-based correlation analysis with step wise 2 method  to determine the number of trip generation and trip attraction that occurs at this time to predict the movement that occurred in the future. Based on the results of the model analysis of trip generation and trip attraction to predict the trip generation and trip attraction in Rokan Hulu regency  that is the trip Generation (Y1) = 8081,628 + 40,025X5 +148,196X6 + 2258,231X7-1714,622X8 + 5236,070X9 + 283,860X10- 19684,192 X11 + 512,363X12-743,228X13 +180,360X15 with coefficient of determination value R2 = 0,923. While trip attraction (Y2) = 12596,939+ 67,752X3-133,661X6 + 1632,938X7-852,571X8 + 12121,156X9 + 231,056X10-17170,524X11+ 597,632X12-22103,205X13 + 193,0097X15 with the coefficient of determination R2 = 0.915. Key words: model, trip generation, trip attraction